Identifying ways to improve diabetes management during cancer treatments (INDICATE): protocol for a qualitative interview study with patients and clinicians. Issue 2 (22nd February 2022) - Ashley, Laura; Kassim, Saifuddin; Kellar, Ian; Kidd, Lisa; Mair, Frances; Matthews, Mike; Price, Mollie; Swinson, Daniel; Taylor, Johanna; Velikova, Galina; Wadsley, Jonathan
Abstract : Introduction: A large and growing number of patients with cancer have comorbid diabetes. Cancer and its treatment can adversely impact glycaemic management and control, and there is accumulating evidence that suboptimal glycaemic control during cancer treatment is a contributory driver of worse cancer-related outcomes in patients with comorbid diabetes. Little research has sought to understand, from the perspective of patients and clinicians, how and why different aspects of cancer care and diabetes care can complicate or facilitate each other, which is key to informing interventions to improve diabetes management during cancer treatments. This study aims to identify and elucidate barriers and enablers to effective diabetes management and control during cancer treatments, and potential intervention targets and strategies to address and harness these, respectively. Methods and analysis: Qualitative interviews will be conducted with people with diabetes and comorbid cancer (n=30–40) and a range of clinicians (n=30–40) involved in caring for this patient group (eg, oncologists, diabetologists, specialist nurses, general practitioners). Semistructured interviews will examine participants' experiences of and perspectives on diabetes management and control during cancer treatments. Data will be analysed using framework analysis. Data collection and analysis will be informed by the Theoretical Domains Framework, and related Theory and Techniques Tool and Behaviour Change Wheel, to facilitate examination of a comprehensive range of barriers and enablers and support identification of pertinent and feasible intervention approaches. Study dates: January 2021–January 2023. Ethics and dissemination: The study has approval from National Health Service (NHS) West Midlands—Edgbaston Research Ethics Committee. Findings will be presented to lay, clinical, academic and NHS and charity service–provider audiences via dissemination of written summaries and presentations, and published in peer-reviewed journals. Findings will be used to inform development and implementation of clinical, health services and patient-management intervention strategies to optimise diabetes management and control during cancer treatments.